2017
DOI: 10.1122/1.4979099
|View full text |Cite
|
Sign up to set email alerts
|

Design and operation of a Rayleigh Ohnesorge jetting extensional rheometer (ROJER) to study extensional properties of low viscosity polymer solutions

Abstract: The Rayleigh Ohnesorge Jetting Extensional Rheometer (ROJER) enables measurement of very short relaxation times of low viscosity complex fluids such as those encountered in ink-jet printing and spraying applications. This paper focuses on the design and operation of the ROJER. The performance of two nozzle designs are compared using Newtonian fluids alongside a study using computational fluid dynamics (CFD). Subsequently a disposable nozzle is developed that overcomes issues of blockage and cleaning.The operab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Though such measurements are possible with ROJER or the jetting‐based rheometer, high shear rates within the nozzle can perturb the chains. In both CaBER and ROJER, the initial deformation and preshear applied can influence the measurement of extensional relaxation time and extensional viscosity values . The influence of extensibility on overall pinch‐off dynamics is illustrated best by contrasting the pinch‐off dynamics of four solutions with a similar degree of overlap ( c/c4) but different molecular weights, as shown in Figure (d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though such measurements are possible with ROJER or the jetting‐based rheometer, high shear rates within the nozzle can perturb the chains. In both CaBER and ROJER, the initial deformation and preshear applied can influence the measurement of extensional relaxation time and extensional viscosity values . The influence of extensibility on overall pinch‐off dynamics is illustrated best by contrasting the pinch‐off dynamics of four solutions with a similar degree of overlap ( c/c4) but different molecular weights, as shown in Figure (d).…”
Section: Resultsmentioning
confidence: 99%
“…For Newtonian fluids, the complex interplay of inertial, viscous and capillary stresses before and after breakup leads to neck thinning dynamics that can often be described by universal scaling laws, and self‐similar neck evolution manifested in experiments . Stream‐wise velocity‐gradients associated with extensional flows arise in thinning liquid necks spontaneously formed during printing, spraying and atomization and fiber spinning . Although extensional viscosity ( ηE) that quantifies the resistance to extensional flows is only three times the shear viscosity for Newtonian fluids as was pointed out by Trouton, the extensional viscosity for polymer solutions can be orders of magnitude higher (10 4 –10 6 reported for dilute polymer solutions) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, the question arises whether this new time scale of 2λ describes also other jetting experiments (as the ROJER technique), or if the so far also for jetting experiments employed time scale of 3λ [34,36,37,40] remains correct at higher jet velocities We ) 1. Quantitative experiments of viscoelastic fluids are scarce [2] and the only direct comparison of relaxation times obtained with jetting and regular capillary thinning experiments on the same fluid has recently been reported by Harlen and co-workers [41]. A reason for this scarcity of experimental data is that the two experiments are probing very different time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the polymer concentration, the dilute, semidilute, and concentrated regimes are distinguished (Teraoka 2002). Capillary thinning of dilute solutions was investigated in many previous studies (Ng et al 1996;Bazilevskii et al 1997;Entov and Hinch 1997;Stelter et al 2000Stelter et al , 2002Gupta et al 2000;Walker 2001, 2002;Rothstein and McKinley 2002;Rodd et al 2005;Tirtaatmadja et al 2006;Clasen et al 2006;Tembely et al 2012;Keshavarz et al 2015;Greiciunas et al 2017). For polystyrene in an oligomeric styrene solution, showed that λ e show molecular weight dependence according to the Zimm model.…”
Section: Introductionmentioning
confidence: 99%